Pengaruh Job Stress, Toxic Workplace, Performance, dan Intention to Leave Melalui Employee Engagement - Augustine, Intanie; Daud, Ilzar; Listiana, Erna; Hendri, Irfani; Marumpe, Dody Pratama (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explore how job stress and adverse work environment affect the exit intention of Generation Z employees, considering both direct and indirect influences mediated by their performance and engagement at work. The study used a quantitative approach and was conducted in Indonesia. Respondents consisted of 200 Gen Z employees aged 18–27 who currently work at various startups. Data were collected through an online questionnaire and analyzed using Partial Least Squares (PLS) with the help of SmartPLS software 4. Findings showed that job stress and a toxic work environment had a significant and positive influence on the intention to leave. Additionally, employee engagement plays an important role in mitigating the negative impact of stress and toxicity, while employee performance also serves as a mediating variable that influences employees’ decisions to stay or leave. All hypotheses put forward in this study are accepted and reliable. This study is limited to young employees (Gen Z) working in startup companies in Indonesia. The study did not include other generational or industrial groups, as well as did not consider additional factors such as career development opportunities or organizational justice that may also influence intentions to leave.